Enhancing the resolution of the forward second harmonic imaging using the two-photon laser scanning microscope - Reshak, Ali Hussain (Micron (Oxford, England, 2009)
UNLABELLED: The effect of increasing the numerical aperture and changing the immersion imaging medium of the objective in the forward second harmonic imaging of the grana and intergranal parts of chloroplasts in the leaves of shade moss Plagiomnium affine plant were demonstrated. Also the enhancement of the forward second harmonic generation images and simultaneously records the forward and backward second harmonic signals were demonstrated. The second harmonic signals in the forward and backward directions are generated by a tightly focused linearly polarized femtosecond pulses laser. CONCLUSIONS: Forward second harmonic signals were successfully enhanced by capturing higher order of diffraction rays from the samples using high numerical aperture water immersion objective.
Keywords: Microscopy, Fluorescence; Plant Leaves; Lenses; Bryopsida; Microscopy, Confocal; tylakoidy; Image Enhancement; Thylakoids; fluorescenční mikroskopie; polarizační mikroskopie; konfokální mikroskopie; lasery; listy rostlin; mechy; Photons; fotony; Lasers; Microscopy, Polarization; čočky; vylepšení obrazu